Degradation of chiral neonicotinoid insecticide cycloxaprid in flooded and anoxic soil. (January 2015) - Liu, Xuanqi; Xu, Xiaoyong; Li, Chao; Zhang, Hanxue; Fu, Qiuguo; Shao, Xusheng; Ye, Qingfu; Li, Zhong
Highlights: CYC showed the short persistence in the submerged and anoxic soils. CYC produces a series of transformation products affected by soil properties. Stereoselective degradation pathways between two CYC enantiomers were not observed based on the experimental data. The time-dependent dynamic changes of CYC transformation products were explained. Abstract: Cycloxaprid (CYC), with two stereogenic centers from oxabridged ring, is a novel potent neonicotinoid insecticide. The investigation of relevant transformation products (TP s) is critical for the risk evaluation of CYC on environment impact and further regulatory decisions. In this study, stereoselective soil metabolism of CYC enantiomers was investigated using isotope labeling techniques. Liquid scintillation counting with LC–MS/MS was used to identify and quantify the major transformation products (TP s) of CYC enantiomers in four various soils under anoxic and flooded condition. Most of CYC had been transformed in four soils at 5 d after treatment. Furthermore, CYC was found converted to a range of transformation products, which exhibited soil-specific dynamic changes. Cleavage of the oxabridged seven-member ring, reductive dechlorination in the chloropyridinyl and cleavage of C–N between the chloropyridinylmethyl and imidazalidine ring are the main transformation pathways of CYC. It is presumed that acidic condition may conduce to form the cleavage product of oxabridged seven-member ring. However, abiotic or biotic stereoselective persistence of TP s in all soils was not observed from the experimental data and may be attributed to the unstable oxabridged ring.